Keislaman Suku Baduy Banten: Antara Islam dan Slam Sunda Wiwitan - Kiki Muhamad Hakiki (Refleksi, 2015)
The focus of this research is to uncover Islamic life of Baduypeople, who are divided into three: Baduy Dalam(internal Baduy) which iscalled Tangtu, and Baduy Luar (external Baduy)which is divided into twotribes i.e. Panampingand Dangka. Compared to other first two Baduys,Baduy Dangka is more intensive in having Islamization. However, in fact,all Baduys have close relations to Islam, due to their original principle theso-called Sunda Wiwitan, or Slam Sunda Wiwitan. Nevertheless, SundaWiwitan (Slam Sunda Wiwitan) is still simple and sincretic. Even thoughone of Baduy is Islamizing itself, the relationship with other Baduys isrespectable, and religious toleration in between them is well-mannered aswell.